An Error Analysis of Students in Writing Narrative Text - Juliani Dameria Pardosi; Renstra Emitha Veronika Br. Karo; Owinike Anggun S. Sijabat; Hotmatua Pasaribu; Natalia Widya Pasca Tarigan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This research is aimed to find out the typical errors on students in writing narrative text by using simple past tense at grade IX of SMP SwastaTalitakum Medan. The researchers used a descriptive qualitative method in this research. Based on the research findings, it can be concluded that the errors of misinformation are the most frequent errors in which the ninth grade students committed 233 errors in regular verb. Moreover , it was followed by errors of misinformation with 150 errors, addition with 38 errors, omission with 29 errors and misordering with 16 errors. Then errors in regular verb, it was followed by errors of misordering with 36 errors, omission with 38 errors, addition with 56 errors and misinformation with 156 errors. It can be concluded that after analyzing through the research, the writer got the data about students’ errors, which are commonly made in narrative writing using simple past. Their errors are misinformation, addition, omission and misordering. Keywords: error analysis, simple past tense